STUDY OF TYPOLOGY OF VERTICAL RESIDENTIAL SPACE PATTERNS IN JAKARTA - Gunawan, Wawan; Purwantiasning, Ari Widyati (Border: Jurnal Arsitektur, 2021)
The population density in Jakarta can be seen from the number of people who are increasing every year and increasing the population density living in Jakarta. High urbanization affects the process of urban development, population development and the need for housing that requires a lot of land in the Jakarta area. The government and the private sector in dealing with these problems provide a decent place to live for the community by building vertical housing. Vertical development in the form of flats for residents is considered capable of increasing efficiency, effectiveness of space utilization and saving land so that land can be used for open space or other public spaces. In this study, the author tries to answer the problems regarding the identification of residential space patterns and the typology of flats in the three case studies. This study uses a qualitative descriptive method in which the author will describe and identify every aspect contained in this study based on the theoretical basis that was appointed as a guide. In this study, it was found that user activity in the flats resulted in groupings called zoning which included private, semi-private / semi-public, public, service areas, and circulation areas. Because the flat is a shared house in one building mass, the public zoning area tends to be larger and the residents gather in public areas that have been facilitated.